Identificación de aspectos e impactos ambientales generados por las actividades, productos y servicios prestado en la estación de servicio (2024)
The purpose of this work is to identify the environmental impacts that may be generated by retail services provided by a service station. The content includes the identification of the activities, products and services developed. This evaluation will be consolidated under the identification and assessment of the tasks of the project, in which the causes of the positive and negative impact on the environment can be seen. After reviewing the methodologies currently available to carry out the matrix, the decision was made to base it on that of Vicente Conesa Simplified.